CREDIT RISK-TAKING AND CAPITAL POSITION: EVIDENCE FROM TWO-STAGE REGRESSION - Suhartono Suhartono (Journal of Economics, Business, and Accountancy Ventura, 2012)
Research on credit risk and its relationship with capital in a company is important. This isbecause the information about such thing can be considered very beneficial. This study examinesthe relationship between risk and capital in Indonesia Banking Market. It tested whetherbank credit risk taking is correlated with its capital position. In this study, risk and capitalwere based on accounting ratios. Data for the study were taken from Banks cope databasefor the period 2003 to 2008. A two-stage-Regression analysis was used to estimate the relationship.On the risk taking model, it is correlated with ex post risk, portion of loan loss provisionto capital (RISKCAP), and ratio of net loans to asset (NLTA), and negatively to sizeand inefficiency. On the capital equation, there is negative relationship with risk taking butnot with inefficiency. Asset size has negative impact on capital positions and profitable bankshold more capital. It is clear that risk taking is not influenced by capital and capital is negativelydetermined by risk taking. In short, the relationship between risk taking and capital isnot two-way but one way.